Le projet de réforme du Code civil et l’assurance : critique de certaines dispositions - Moreau, Rémi (Assurances, 1991)
This article presents a critical study of Bill 125 which reforms the Civil Code relating to insurance law. According to the author, this Bill, tabled in 1990, has taken into account some of the recommendations from the insurance industry on the Draft Bill presented in 1987. But many areas remain unchanged. Specific provisions continue to be problematic in both where the interpretation and application of the insurance contract are concerned, and some of them are unfavorable to the insured or contrary to fundamental principles.